1992
DOI: 10.1164/ajrccm/146.5_pt_1.1294
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia-induced Airway Remodeling in Immature Rats: Correlation with Airway Responsiveness

Abstract: We recently found that exposure of 21-day-old rats to hyperoxia (> 95% O2 for 8 days) significantly increased in vivo airway cholinergic responsiveness and that O2 exposure also increased airway epithelial and smooth muscle layer thicknesses in a separate cohort of animals. There was substantial variation in the magnitude of both the functional and structural responses to hyperoxia. The present study was designed to test whether the magnitude of O2-induced airway remodeling could account for individual differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
17
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 8 publications
4
17
0
Order By: Relevance
“…Intriguingly, some of these changes are permanent, as normal lung structure and function are not restored when newborn animals are returned to room air (9)(10)(11). Hyperactive airways with increased thickness of the underlying smooth muscle have also been reported in 21-day-old rats exposed to and recovered from greater than 95% oxygen (12,13). We reported that exposure of newborn mice to greater than 85% oxygen between Postnatal Days 1 and 4 causes permanent alveolar simplification and altered lung compliance in adult mice (14,15).…”
mentioning
confidence: 99%
“…Intriguingly, some of these changes are permanent, as normal lung structure and function are not restored when newborn animals are returned to room air (9)(10)(11). Hyperactive airways with increased thickness of the underlying smooth muscle have also been reported in 21-day-old rats exposed to and recovered from greater than 95% oxygen (12,13). We reported that exposure of newborn mice to greater than 85% oxygen between Postnatal Days 1 and 4 causes permanent alveolar simplification and altered lung compliance in adult mice (14,15).…”
mentioning
confidence: 99%
“…Studies examining mechanisms of hyperoxia-induced airway hyperresponsiveness havc focused on contractile mechanisms (20)(21)(22)28) although excessive airway narrowing could be due to impaired relaxation (29). The most important finding of this study was that in newborn guinea pig airways, in vivo exposure to hyperoxia decreased the relaxing ability of loop diuretics, ethacrynic acid and furosemide, and the P,-adrenergic receptor agonist salbutamol.…”
Section: Discussionmentioning
confidence: 79%
“…Hyperoxia is known to cause pulmonary pathology and dysfunction in many animals (21)(22)(23)(24)27), although the mechanism of this injury is not fully understood. Studies examining mechanisms of hyperoxia-induced airway hyperresponsiveness havc focused on contractile mechanisms (20)(21)(22)28) although excessive airway narrowing could be due to impaired relaxation (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations